(untitled) (Bangladesh Journal of Agricultural Research, 2018)
Efficacy of rice bran, wheat bran, grass pea bran and their combinations with or without mustard oilcake (MOC) were tested as substrate of Trichoderma harzianum based bio-fungicides for the management of foot and root rot disease of cauliflower caused by Sclerotium rolfsii in the seedbed during three consecutive growing seasons from 2011 through 2014 in the net house of Bangladesh Agricultural Research Institute, Gazipur. The seedbed soil was inoculated with pathogen S. rolfsii colonized on barley grain before treatment with T. harzianum based bio-fungicides. The results of three years trial revealed that T. harzianum based bio-fungicides effectively reduced pre-emergence and post-emergence mortality of cauliflower seedling in seedbed. Besides, vegetative growth of cauliflower seedlings viz. shoot length, shoot weight, root length and root weight were enhanced significantly by different substrates based T. harzianum bio-fungicides in S. rolfsii sick seedbed. The substrates rice bran, wheat bran, grass pea bran and their combination with mustard oilcake (MOC) were equally suitable for effective formulation of T. harzianum bio-fungicides against foot and root rot disease of cauliflower in seedbed. Bangladesh J. Agril. Res. 42(4): 609-620, December 2017